Resonant Power Converter for Ultrasonic Piezoelectric Converter. - Schulte, Thomas; Fröhleke, Norbert; Kauczor, Christopher (ACTUATOR 2002)
Ultrasonic piezoelectric converters (UPC) require adequate power supplies providing high frequency output voltage of several hundred volts and a total output power up to several kilowatts. Several concepts are conceivable but the potential of optimisation adopting a certain concept depends on the electrical terminal behaviour of the UPC. In this contribution the operating behaviour ofUPC is discussed with respect to their transfer function, the necessary excitation and their terminal behaviour. The latter definies the demands for the power supply, while considering different parameter combinations for bandwidth, quality and piezoelectric capacitance. The main part of this contribution is concerned with the development and realisation of a laboratory power supply for UPC, which is of resonant type.